FMISO-PET-derived brain oxygen tension maps: application to glioblastoma and less aggressive gliomas - Chakhoyan, Ararat; Guillamo, Jean-Sebastien; Collet, Solène; Kauffmann, François; Delcroix, Nicolas; Lechapt-Zalcman, Emmanuèle; Constans, Jean-Marc; Petit, Edwige; MacKenzie, Eric T.; Barré, Louisa; Bernaudin, Myriam; Touzani, Omar; et al. (Scientific reports, 2017)
Quantitative imaging modalities for the analysis of hypoxia in brain tumors are lacking. The objective of this study was to generate absolute maps of tissue p t O 2 from [ 18 F]-FMISO images in glioblastoma and less aggressive glioma patients in order to quantitatively assess tumor hypoxia. An ancillary objective was to compare estimated p t O 2 values to other biomarkers: perfusion weighted imaging (PWI) and tumor metabolism obtained from 1 H-MR mono-voxel spectroscopy (MRS). Ten patients with glioblastoma (GBM) and three patients with less aggressive glioma (nGBM) were enrolled. All patients had [ 18 F]-FMISO and multiparametric MRI (anatomic, PWI, MRS) scans. A non-linear regression was performed to generate p t O 2 maps based on normal appearing gray (NAGM) and white matter (NAWM) for each patient. As expected, a marked [ 18 F]-FMISO uptake was observed in GBM patients. The p t O 2 based on patient specific calculations was notably low in this group (4.8 ± 1.9 mmHg, p < 0.001) compared to all other groups (nGBM, NAGM and NAWM). The rCBV was increased in GBM (1.4 ± 0.2 when compared to nGBM tumors 0.8 ± 0.4). Lactate (and lipid) concentration increased in GBM (27.8 ± 13.8%) relative to nGBM (p < 0.01). Linear, nonlinear and ROC curve analyses between p t O 2 maps, PWI-derived rCBV maps and MRS-derived lipid and lactate concentration strengthens the robustness of our approaches.